The force of finance triumph of the capital markets - Brenner, Reuven (Texere, 2002)
Brenner examines whether the 21st Century will be another American century; the financial and regulatory changes required to adjust to a more mobile world; religion and nationalism; the connection between democracy and financial markets; and the links between higher education and myths societies live by. And all this is in clear, compelling writing that is devoid of jargon.